A Marine Gravimeter Based On Precise Single-point Positioning Technology In Pacific Ocean. Issue 4 (April 2020) - Xu, Xiao; Wu, Meiping; Cai, Shaokun; Yu, Ruihang; He, Shaofei; Lu, Qi
Abstract: Marine gravity measurement is one of the methods of marine geophysical measurement. The marine test used the SGA-WZ02 gravity meter independently developed by the National University of Defence Technology (NUDT), about 60 days of maritime tests were conducted in the Pacific Ocean from July to September 2019. The purpose of the test is to evaluate the feasibility of this gravimeter for marine gravity measurement and the accuracy of data processing using GNSS precision point positioning technology (PPP) in the later stage. The test area is located in a strait in the Pacific Ocean. The total area of the test area is about 2840km2 and the total distance is about 1074km. Among them, 7 repeat lines were measured, each distance was about 14.5km, and the ship speed was about 27.78km/h. In this paper, GNSS precision single-point positioning technology is used to evaluate the quality of the data of 7 repeated lines. After 100s low-pass filtering, the standard deviation of the accuracy within the SGA-WZ02 gravity meter is 0.56mGal, and the median error is 0.60mGal. The test results show that the SGA-WZ02 strapdown gravimeter can be used for the measurement of marine gravity field. The data processing algorithm based on precise single-point positioning technology meets the accuracy requirements of gravity measurement.